2013
DOI: 10.4088/jcp.13f08707
|View full text |Cite
|
Sign up to set email alerts
|

Famotidine Augmentation in Schizophrenia: Hope or Hype?

Abstract: Each month in his online column, Dr Andrade offers practical knowledge, ideas, and tips in psychopharmacology to JCP readers in psychiatric and general medical settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Nevertheless, H 2 R agonists hold great potential as they may cover both the positive and negative symptoms of schizophrenia and may be feasible for direct clinical application. Moreover, there is evidence of H 2 R antagonist famotidine augmentation of antipsychotic medications in schizophrenia patients, but some randomized controlled trials of famotidine did not show consistent efficacy in treating the symptoms of schizophrenia ( 55 58 ). Some evidence suggests that the benefits of famotidine for schizophrenia may not arise from H 2 R antagonism ( 11 , 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, H 2 R agonists hold great potential as they may cover both the positive and negative symptoms of schizophrenia and may be feasible for direct clinical application. Moreover, there is evidence of H 2 R antagonist famotidine augmentation of antipsychotic medications in schizophrenia patients, but some randomized controlled trials of famotidine did not show consistent efficacy in treating the symptoms of schizophrenia ( 55 58 ). Some evidence suggests that the benefits of famotidine for schizophrenia may not arise from H 2 R antagonism ( 11 , 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous article in this column suggested that famotidine augmentation may not be of much benefit. 2 The present article examines 2 other innovative augmentation treatments: nonsteroidal anti-inflammatory drugs (NSAIDs) and 5-HT 3 serotonin receptor antagonists.…”
Section: Introductionmentioning
confidence: 99%